2018
DOI: 10.1177/0267659118793249
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary bypass prime composition: beyond crystalloids versus colloids

Abstract: Use of hyperosmolar CPB prime resulted in a dramatic and instant elevation of the plasma osmolality. Rapid changes in plasma osmolality are associated with organ dysfunction (e.g. osmotic demyelination syndrome), therefore, effects on plasma osmolality related to the CPB prime composition should be recognised. Influence on organ function and clinical outcome warrants further investigations. - Clinical Trials.gov (NCT03060824). Changes in Plasma Osmolality Related to the Use of Cardiopulmonary Bypass With Hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…However, the osmolality increased significantly during CPB in all the patients, but only to a level slightly above the normal range, and it remained slightly elevated throughout surgery. This finding is in line with the previous study by Malmqvist et al The much less pronounced increase in osmolality in our study, compared to that reported by Malmqvist et al, may be due to differences in the prime solutions. In addition, the high potassium content of the cardioplegia solution and substitutional treatment with electrolytes per‐ and postoperatively in our study may have contributed to the increase in osmolality.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, the osmolality increased significantly during CPB in all the patients, but only to a level slightly above the normal range, and it remained slightly elevated throughout surgery. This finding is in line with the previous study by Malmqvist et al The much less pronounced increase in osmolality in our study, compared to that reported by Malmqvist et al, may be due to differences in the prime solutions. In addition, the high potassium content of the cardioplegia solution and substitutional treatment with electrolytes per‐ and postoperatively in our study may have contributed to the increase in osmolality.…”
Section: Discussionsupporting
confidence: 94%
“…Changes in plasma osmolality during cardiac surgery have been poorly investigated. The use of hyperosmolar CPB prime has been reported to result in a dramatic elevation of the plasma osmolality, which may have negative effects on the central nervous system . No studies on the impact of mannitol on plasma osmolality following CPB could be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Standard 13.1: The Perfusionist shall consider the impact the prime has on the smaller circulating blood volume of the pediatric patient and its effect on: electrolyte levels colloid osmotic pressure coagulation Standard 13.2: When priming with exogenous blood, a circuit prime gas and electrolyte levels shall be obtained prior to initiation of bypass and adjustments made to correct any physiologic abnormalities. 21,22 Guideline 13.1 : When priming with exogenous blood, the use of prebypass ultrafiltration (preBUF) or washed red blood cells should be used during priming procedure. 23 -28 Guideline 13.2 : The perfusionist should consider matching prime composition to the individual patient values. …”
Section: Resultsmentioning
confidence: 99%
“…Standard 13.2: When priming with exogenous blood, a circuit prime gas and electrolyte levels shall be obtained prior to initiation of bypass and adjustments made to correct any physiologic abnormalities. 21,22…”
Section: Resultsmentioning
confidence: 99%